Synergistic anti-breast cancer effect of pulsatilla saponin D and camptothecin through interrupting autophagic–lysosomal function and promoting p62-mediated ubiquitinated protein aggregation. (27th August 2019) - Wang, Kai; Tu, Yanbei; Wan, Jian-Bo; Chen, Meiwan; He, Chengwei
Abstract: Autophagy is an evolutionarily conserved mechanism to protect the cells from unfavorable environmental conditions. Inhibition of autophagy has been contemplated as a novel strategy to enhance anticancer efficacy of existing chemotherapeutic agents. We previously reported that pulsatilla saponin D (PSD) was a potent autophagy inhibitor. However, its anticancer potential as adjuvant and underlying mechanisms are still unknown. In this study, we identified that PSD induced the formation of autophagosome in MCF-7 and MDA-MB-231 breast cancer cells. However, PSD alone and particularly co-treatment with camptothecin remarkably increased p62 protein levels, indicating that PSD strongly inhibited the autophagic cargo degradation. The mechanistic study indicated that PSD profoundly abolished the co-localization of EGFP-LC3 and lysosomal-specific probe LysoTracker Red, suggesting that the autophagosome–lysosome fusion was blocked by PSD, which is similar to the action of chloroquine. In addition, PSD significantly increased lysosomal pH and inhibited the activation of lysosomal cathepsins in both breast cancer cell lines. Furthermore, the accrued p62 resulted in accumulation of ubiquitinated proteins owing to the interaction with p62 and delivery to the malfunctioned autophagosome by PSD. Finally, we demonstrated that PSD synergistically enhanced the anticancer activity of camptothecin (CPT) in cultured breast cancer cells and in mouse xenograft tumor models. Our results indicated that PSD inhibited autophagic flux via blocking autophagosome–lysosome fusion and lysosomal acidification, which may confer a synergistic anti-breast cancer activity of PSD and CPT. Abstract : PSD synergistically enhanced the anticancer activities of camptothecin in vitro and in vivo via interrupting autophagic–lysosomal function and inducing p62-mediated ubiquitinated protein aggregation. These effects imply the potential application of PSD in anti-breast cancer therapy as an adjuvant agent.